Analysis of the Management of Cleft Lip Surgery with the Characteristics of Patients with Cleft Lips or Without Cleft Palatum in Nort Sumatra - Samuel J.H.T Rajagukguk; Christina J.R.E Lumbantobing; Tan Suyono (CV. Inara, 2024)
Clefts are the most common type of congenital abnormality on the face. This condition can cause medical, psychological, and social problems in individuals and families. Several previous studies have yielded results in the form of a large number of cleft sufferers who come for treatment at a late age. This can affect the outcomeof the management given. The characteristics of cleft patients in Indonesia, especially in Medan City, are still very limited. Therefore, researchers have the desire to be able to do research in this field. patients with or without cleft palate who were managed by Smile Train Indonesia together with the Horas Sehat Foundation at hospitals in North Sumatra based on:(1) type of cleft, (2) location of the cleft defect, (3) Gender, (4) Treatment time, and (5) Type of operation. design. The sample for this study was secondary data on 193 cleft patients who were managed by Smile Train Indonesia together with the Horas Sehat Foundation at hospitals in North Sumatra in the 2017 – 2022 period. palate based on the type of cleft was labiognatopalatoschizis with a total of 115 patients (59.6%), based on the location of the defect was a unilateral defect (left side) of 98 patients (50.8%), based on gender was male with a total of 130 patients (67.4%), based on the time of treatment category was the late labioplasty category with a total of 54 patients (28%), and based on the type of surgery the most was the type of primary cleft palate repair surgery with a total of 56 people (29%). from previous studies.